Normative Scores for the NIH Toolbox Dynamic Visual Acuity Test from 3 to 85 Years - Li, Carol; Beaumont, Jennifer L.; Rine, Rose Marie; Slotkin, Jerry; Schubert, Michael C. (Frontiers in Neurology, 2014)
As part of the National Institutes of Health Toolbox initiative, a computerized test of dynamic visual acuity (cDVA) was developed and validated as an easy-to-administer, cost- and time-efficient test of vestibular and visual function. To establish normative reference values, 3,992 individuals, aged 3 to 85 years, without vestibular pathology underwent cDVA testing at multiple clinical research testing facilities across the United States. Test scores were stratified by sociodemographic characteristics. cDVA was worse in males (p < 0.001) and those subjects 50 years or older, while there was no difference in DVA across age groups binned from 3 – 49 years. Furthermore, we used these normative cDVA data as a criterion reference to compare both the long (validated) and short versions of the test. Both versions can distinguish between those with and without vestibular pathology (p = 0.0002 long; p = 0.0025 short). The intraclass correlation coefficient between long and short cDVA tests was 0.86.